The Ijtihad Methodology of the Persatuan Islam Hisbah Council In the Determination of Islamic Law - Mugni Muhit; Jajang Herawan; Ending Solehudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research examines and studies the Ijtihad of the Persatuan Islam Hisbah Council in determining Islamic Law. Persatuan Islam is one of the renewal movements that was established in 1923 AD. Persatuan Islam conducted ijtihad through the Persis Ulama Council which later changed its name to the Persatuan Islam Hisbah Council. The Hisbah Council is an Persatuan Islam Legal Institution that functions as a council of consideration, sharia studies, and fatwas in the Persatuan Islam jam'iyyah. The legal studies of the Persatuan Islam Hisbah Council have produced many Islamic legal thoughts, including the law of prayer in two languages, the law of Friday prayer for travelers, raising hands when praying, the position of zakat and taxes, and waqf money, as well as inheritance from non-Muslims. The method of the Hisbah Council in making legal decisions is to base it on the Qur'an and Sahih Hadith, as the main reference and reference for determining Islamic law, and to make ijtihad on issues that are not found in the Qur'an and Hadith of the Prophet.